Determinants of internal governance quality: Evidence from corporations in Ethiopia - Yrgalem Gebreslassie Adane; Tadesse Getacher Engida; Yitbarek Abrha Asfaw; Hossein Azadi; Steven Van Passel (Cogent Economics & Finance, 2018)
The study analysed the factors that affect the internal governance quality of corporations in Ethiopia. It performed an ordered logistic regression analysis on a randomly selected sample of 76 corporations to analyse the effect of the ownership structure, form of ownership (private or government), leverage, corporate size, and sales growth on the internal governance quality score (IGQS). The governance quality score was measured using 20 indices categorized into four perspectives: disclosure, board characteristics, ethics, and shareholder rights. In this study, a significant positive effect of the corporate size and sales growth on the IGQS was found. In addition, government-owned corporations were found to perform better than privately owned corporations. It is recommended that appropriate authorities and officials should encourage the use of the corporate governance system in privately owned corporations and the convergence of internal governance quality of the two groups of corporations to the highest level.
Keywords: 330; corporation; ownership structure; governance; management; development policy